Ecology and management of Bactericera cockerelli and Candidatus Liberibacter solanacearum in New Zealand - Jessica VEREIJSSEN (Journal of Integrative Agriculture, 2020)
The psyllid Bactericera cockerelli was first reported in New Zealand in 2006 and spread quickly throughout all potato growing regions. In 2009, B. cockerelli was associated with the plant pathogenic bacterium Candidatus Liberibacter solanacearum, the putative causal agent of zebra chip disease in potato. Both the psyllid and the bacterium have non-crop host plants which can serve as reservoirs when the crop is not available. Growers apply different management strategies that fit integrated pest management programmes to manage B. cockerelli and subsequently lower incidence of zebra chip disease in potato crops. Despite best management efforts, complete control of B. cockerelli and zero incidence of zebra chip disease are not achievable at the current time.